Comparative Study Between Pid Controller And Fuzzypid Controller For Speed Control Of Pm Bldc Motor Drive - Abidin, Muhammad Firdaus Zainal (2013)
This research focuses on a comparative study between PID controller and FuzzyPID controller for speed control of permanent magnet brushless (PM BLDC) motor drive. PM BLDC motors are more popular over the other types of electric motors which make PM BLDC motors widely used in many applications. It is well known that most of the industrial applications used conventional PID controllers. Nowadays, PID controller is considered as a conventional system due to the existence of several intelligent controls such as Fuzzy Logic Control (FLC). However, PID controller still remains a valid approach to implementing a feedback control system. When the nonlinearities of the system are the major issues in motor control, it could be more convenient to improve the PID control strategy rather than to work out complicated dynamic models which require sophisticated control strategies. Thus, FuzzyPID controller has been proposed and discussed for speed control of PM BLDC motor. Motor speed responses are studied under different operating conditions including response to small and large step speed reference change, and response to step load application. Simulation results are supplemented with a set of experimental results, obtained using PID and FuzzyPID controllers respectively. The experimental results showed that FuzzyPID controller provides a superior speed response with approximately 0.1 s faster of the rise time and settling time as well as managed to reduce the amount of overshoot until 20% compared to the PID controller.